2013
DOI: 10.4012/dmj.2012-300
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of Fuji VII and a resin sealant in children at high and low risk of caries

Abstract: The purpose was to compare the retention and caries preventive effect of Fuji VII and a resin-based sealant in children at high risk (HR) and low risk (LR) of caries. Fifty-seven schoolchildren (150 teeth) with completely erupted bilateral permanent first molars were included. The study was a split-mouth, randomized trial. Sealant retention and caries were evaluated after 6 months, 1 year and 2 years. After 2 years, there was no statistically significant difference in the incidence of caries between Fuji VII a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
(48 reference statements)
1
19
0
2
Order By: Relevance
“…In the present study, rubber dam isolation was not used, as had been reported for many other sealant studies. 20,27,29,30,31,32 Th is deviat ion from the goi ng protocol for resin-based procedures is justified since it was shown that rubber dam does not improve the retention of resin-based sealants. 33 It was possible to blind treatment for the children, as only one kind of treatment was performed at each of the schools.…”
Section: Discussion Methodologymentioning
confidence: 99%
“…In the present study, rubber dam isolation was not used, as had been reported for many other sealant studies. 20,27,29,30,31,32 Th is deviat ion from the goi ng protocol for resin-based procedures is justified since it was shown that rubber dam does not improve the retention of resin-based sealants. 33 It was possible to blind treatment for the children, as only one kind of treatment was performed at each of the schools.…”
Section: Discussion Methodologymentioning
confidence: 99%
“…Similarly, a field study found no significant difference in the cumulative survival of pit and fissure caries between glass-ionomer and resin-based sealants after two years 30) . Another study reported no significant difference in caries incidence between glass-ionomer and resin-based sealants 33) . However, a clinical study showed that glass ionomer sealants were slightly more efficient in preventing caries than resin-based 32) .…”
Section: Discussionmentioning
confidence: 99%
“…Comparable results were reported in another study in which sealants were provided in a school environment, which found that 93.8% of resinbased sealants were completely lost 3 years after placement 31) . One clinical study and other field studies found that the retention of resin-based sealants was higher than that of glass-ionomer sealants [32][33][34] . For both sealants, the higher survival rate of retention noted in our study could be because both sealants were applied under controlled and dry clinical conditions by a single operator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations